Ground spiders (Araneae, Gnaphosidae) from Jiangxi Province, China - Liu, Ke-Ke; Yan, Jing; Xiao, Qi-xin; Luo, Chong; Xiao, Yong-hong; Fomichev, Alexander A. (ZooKeys)
A list of 26 gnaphosid species belonging to 14 genera collected in Jiangxi Province, China, is provided. Three new species of ground spiders from Jiangxi Province of China are diagnosed, described, and illustrated: Haplodrassus yinae Liu, sp. nov. (male female), Hitobia xiaoxi Liu, sp. nov. (male), and Zelotes dingnan Liu, sp. nov. (male female). Haplodrassus yinae Liu, sp. nov. was previously erroneously recorded in Jiangxi Province as H. montanusYin et al., 2012.